The Monte Carlo Thermal-Physics Coupling Method Based on Functional Expansion Tallies - An Nan; Gou Yuanhao; Luo Hao; Liu Zhaoyuan; Wang Kan (EPJ Web of Conferences)
In the Monte Carlo thermal-physical calculations for nuclear reactors, the precise and effective transfer of data between different meshes is a difficult issue of thermal and physical coupling. Converting two separate meshes and transferring the data is an exceptionally difficult and complex task within the conventional nuclear thermal-physics coupling approach. The newly developed Functional Expansion Tallies (FET) method can obtain the continuous distribution of parameters in the solution space. By applying FET method to nuclear thermal-physics coupling, the no-mesh continuous fission energy distribution can be obtained, which is suitable for more complex meshes. Additionally, the computational memory can be minimized by substituting the data from numerous mesh power distribution data points with the coefficients of the function.